Analysis of Strain State and Cracking of Cocnrete Sleepers - Jokūbaitis, Aidas; Valivonis, Juozas; Marčiukaitis, Gediminas (Journal of Civil Engineering and Management, 2016)
Prestressed concrete sleepers are the most common type of the sleepers used on the railroad. They serve as rail supports and absorb loads induced by trains. Sleepers are important for the durability and safety of the railroad and are exposed to various loads and an agressive environment during exploitation. Therefore, different types of appearing damage can determine their reliability. The article briefly discusses possible causes of damage and the deterioration of prestressed concrete sleepers. End cracking and damage at the rail seat was determined during the inspection of used sleepers. Therefore, the strain state and cracking of the rail seat of the sleeper was analysed under static and dynamic loads. The paper provides the obtained results of experimental research of used and new sleepers.